Diferenciação hepatocítica de células-tronco mesenquimais da medula óssea humana - Penteado, F. C L [UNESP]; Orellana, M. D.; Fontes, A. M.; Kashima, S.; Covas, Dimas Tadeu (My University, 2007)
Some recent articles have reported that mesenchymal stem cells (MSCs) can be induced to express hepatocyte markers by transplanting them into animal models of liver damage, or by in vitro culture with growth factors and cytokines. In this study, the aim is to evaluate the behavior of MSCs subjected to induction of hepatocyte differentiation. The MSCs were isolated from the bone marrow of 4 normal donors, characterized and subjected to both in vitro and in vivo induction of hepatocyte differentiation. The in vitro induced cells showed morphological changes, acquiring hepatocyte-like features. However, the immunophenotype of these cells was not modified. The induced cells exhibited no increase in albumin, cytokeratin 18 or cytokeratin 19 transcripts, when analyzed by real-time RT-PCR. The expression of albumin, cytokeratin 18 and alpha fetoprotein was also unchanged, according to immunofluorescence tests. In vivo, the MSC demonstrated a potential to migrate to damaged liver tissue in immunodeficient mice. Taken together, the results suggest that bone marrow MSCs are incapable of in vitro differentiation into hepatocytes by the approach used here, but are capable of homing to damaged hepatic tissue in vivo, suggesting a role for them in the repair of the liver. This contribution to tissue repair could be associated with a paracrine effect exerted by these cells.

Algumas pesquisas realizadas recentemente relatam que as células-tronco mesenquimais (CTM) podem ser induzidas à aquisição de marcadores hepatocíticos pelo transplante em modelos animais de dano hepático, ou pelo cultivo in vitro com fatores de crescimento e citocinas. O presente estudo teve por objetivo avaliar o comportamento das CTM frente à indução da diferenciação hepatocítica. As CTM foram isoladas da medula óssea de quatro doadores saudáveis, caracterizadas e submetidas ao protocolo de indução à diferenciação hepatocítica in vitro e in vivo. As células induzidas in vitro apresentaram mudanças na sua morfologia, mostrando a morfologia semelhante à do hepatócito, porém, o perfil imunofenotípico não foi modificado. As células induzidas também não apresentaram o aumento dos transcritos de albumina, citoqueratina 18 e citoqueratina 19 quando analisadas por RT-PCR em tempo real, e não alteraram a expressão de albumina, citoqueratina 18 e alfa-fetoproteína como demonstrado por imunofluorescência. Quando analisadas in vivo, as CTM demonstraram o potencial migratório para o tecido hepático danificado de camundongos imunodeficientes. Em conjunto, os resultados sugerem que as CTM da medula óssea não são capazes de se diferenciar em hepatócitos quando estimuladas in vitro pela metodologia utilizada neste estudo, mas são capazes de migrar para o tecido hepático danificado in vivo, o que sugere o seu papel no reparo do fígado. A contribuição para o reparo pode estar associada com o efeito parácrino dessas células. Palavras-chave: célula-tronco mesenquimal; diferenciação hepatocítica; albumina; citoqueratina 18; dano hepático; camundongos imunodeficientes
Hepatocytic differentiation of human bone marrow mesenchymal stem cells
Keywords: Albumin; Cytokeratin 18; Hepatocyte differentiation; Immunodeficient mice; Liver damage; Mesenchymal stem cells; albumin; alpha fetoprotein; cytokeratin 18; animal cell; animal experiment; animal model; animal tissue; cell differentiation; cell isolation; cell migration; cell structure; controlled study; hematopoietic stem cell; human; human cell; immunofluorescence test; immunophenotyping; liver cell; liver injury; mesenchymal stem cell; mouse; nonhuman; normal human; paracrine signaling; protein expression; real time polymerase chain reaction; reverse transcription polymerase chain reaction